Exploring The Interplay of Personality Dimensions and Organizational Culture on Organizational Citizenship Behavior - Zaky Mohammad Mubarok; Imam Machali (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2023)
This research aims to elucidate the intricate relationship between personality dimensions, organizational culture, and their cumulative effect on organizational citizenship behavior (OCB) at Al-Madani Majalengka Islamic Boarding School. Our study designates personality dimensions as the independent variable and organizational citizenship behavior as the dependent variable, with organizational culture serving as a control variable. We adopted a stratified random sampling method, culminating in a sample size of 178 respondents. Data were collected via questionnaires and subsequently analyzed through bivariate correlation techniques and partial correlation methods using SPSS version 26 software. Our bivariate correlation analysis revealed a significant, positive correlation between personality dimensions and organizational citizenship behavior. Simultaneously, partial analysis indicated that organizational culture could mediate the impact of personality dimensions on OCB. Therefore, we concluded that personality dimensions indeed significantly and positively impact OCB. However, to realize the potential of an individual's personality, it is paramount that a conducive organizational culture, encapsulating guidelines, values, and rules, is present to foster OCB at Al-Madani Islamic Boarding School Cikalong Majalengka.